Gustáv Husák and the Foundations of 'Normalization': Slovak, Czechoslovak and Federative Perspectives, 1968–1970. (3rd July 2019) - Poláčková, Zuzana; van Duin, Pieter C.
ABSTRACT: This article tries to analyze the early stages of normalization by looking at three dimensions which simultaneously played a part in this complex post-liberal situation. Important was not only political developments in Czechoslovakia as a whole, but also more specifically the situation in Slovakia, the homeland of Gustáv Husák, both communist and Slovak patriot. The fact that normalization coincided with the onset of federalization of the Czechoslovak state implied that the political instrumentalization of federalization added a further dimension to the complexity of normalization. Husák proved to be the person who was best-prepared to exploit the political opportunities offered by this situation and to take command of the new dynamics in Czechoslovakia after August 1968. However, the complex process of normalization moved forward only slowly, step by step, and Husák had to work hard to bring the situation 'under control'. The article also argues that this was only possible because the new party leader was constantly using a 'populist' discourse of ensuring peace and quiet and eliminating chaos and uncertainty. Husák and the other normalizers may have believed in communist ideology, but they realized that they had to define the situation in other terms as well in order to win over at least a part of the Czechoslovak population.